Uterine artery embolization in the treatment of symptomatic fibroids – state of the art 2018 - Stępniak, Anna (Menopause Review/Przegląd Menopauzalny, 2018)
Uterine fibroids are considered to be the most common benign tumours in females. The vast majority of these tumours are incidental findings and do not require any treatment. Symptomatic fibroids, with ailments such as abnormal uterine bleeding, dysmenorrhoea, pelvic pain, impaired urination, bowel dysfunction, infertility, and recurrent pregnancy loss, are indicated for medical treatment. Surgery remains a first-line treatment of symptomatic uterine fibroids; however, minimally invasive techniques and pharmacological management have become more available and popular. Among minimally invasive techniques uterine artery embolization (UAE) is the most well-established uterine preserving treatment. UAE was first introduced in obstetrics and gynaecology in 1987 and since then many studies have shown the safety and efficacy of UAE in fibroid treatment with low rates of complications. In this review we present a novel approach to UAE, which reflects the current state of knowledge based on recent clinical trials and long-term post-procedural follow-up.